HUBUNGAN PENGETAHUAN DAN PENDAPATAN KELUARGA DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS IDI RAYEUK KABUPATEN ACEH TIMUR TAHUN 2023 - Mariatun Mariatun; Anna Waris Nainggolan; Edy Marjuang Purba (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2024)
Stunting is a national and global nutritional problem that requires attention from various sectors. Each individual's nutrition can be considered as an indicator to determine a person's health status, including the toddler group. Nutrition also has an impact on the level of harmony between a person's physical condition and mental condition. Insufficient knowledge and low family income are thought to be important factors in increasing the risk of stunting. The aim of this research is to determine the relationship between knowledge and family income and the incidence of stunting among toddlers in the work area of ​​the Idi Rayeuk Community Health Center, East Aceh Regency in 2023. This type of research is analytical observational with Cross-Sectional. The population in this study is the population in this study is all toddlers or all toddlers in the Idi Rayeuk Community Health Center Working Area, East Aceh Regency in 2023, a total of 61 people. The sample was taken as a total sampling, namely 61 people. Data analysis was carried out using statistical tests using chi-square, to see the relationship between the independent variable and the dependent variable. The results of the research show that there is a relationship between knowledge and family income (p<0.005) with the incidence of stunting among toddlers in the Idi Rayeuk Community Health Center Working Area, East Aceh Regency in 2023. It is recommended that the Community Health Center provide education to parents so that they have good knowledge of skills in the pattern of take care of toddlers so that the risk of stunting can be reduced.